High-flux soft x-ray harmonic generation from ionization-shaped few-cycle laser pulses - Johnson,A; Austin,D; Wood,D; Brahms,M; Gregory,A; Holzner,K; Jarosch,S; Larsen,E; Parker,S; Struber,C; Ye,P; Tisch,J; et al. (Science Advances, 2018)
Laser driven high harmonic generation provides the only demonstrated route to generatestable, tabletop attosecond X-ray pulses, but with low flux compared to other X-ray tech-nologies. Here we show that higher photon energies and flux can be obtained from highharmonic generation by using higher laser intensities than are typical, strongly ionizing themedium and creating plasma which reshapes the driving laser field. We obtain high harmon-ics capable of supporting attosecond pulses out to photon energies of 600 eV, and a photonflux inside the water window (284 eV to 540 eV) ten times higher than previous attosecondsources. We demonstrate that operating in this regime is key for attosecond pulse generationin the X-ray range, and will become increasingly important as harmonic generation movesto even longer wavelength driving fields.